A modified cohesion method considering fiber bridging. (November 2022) - Ma, Qiwen; Liu, Jianhui; Zhang, Yonggui
Abstract: The fiber bridging characteristics of multidirectional laminates are more obvious than those of unidirectional laminates, which means more fibers will be pulled out of multidirectional laminates. The existence of bridging phenomenon will have a greater impact on the interlaminar fracture toughness. However, the traditional cohesive model cannot characterize the features of fiber bridging well. In this paper, a new modified cohesive model is proposed by considering the nonlinear degradation of the mechanical response of the fibers to the matrix and the bridging stress, modify the mode I cohesive model from the theoretical point of view as well. Based on the modified model, a new functional model is developed to characterize the interlaminar fracture toughness and the traction-separation relationship. Meanwhile, the maximum bridging stresses at different interfaces are calculated. Compared with the original functional model, the modified functional model has a higher fitting accuracy with the steady-state fracture toughness experimental values and can better characterize the traction-separation relationship at different interfaces, which provides a theoretical basis for the modified cohesive model. Highlights: The numerical relationship between the loading displacement and DCBspecimen is derived. The original cohesive model is modified. A numerical model is proposed from the theoretical point of view.